Youth Unemployment and Educational Attainment in South Africa: An Application of Bayesian Vector Autoregressive Model with the Minnesota Prior - Ngundu, Marvellous; Ngalawa, Harold; Derera, Evelyn; Nzimande, Ntokozo (Journal of Ecohumanism, 2025)
Despite near-universal secondary school enrolment, South Africa faces a paradoxical challenge of high youth unemployment, with nearly two-thirds of young people affected. This study seeks to explore the relationship between youth unemployment and educational attainment, specifically focusing on secondary and tertiary education in South Africa. The study employs the Bayesian vector autoregressive model with the Minnesota prior and quarterly frequency data from 2008 to 2022. In line with the human capital theory, which hypothesizes that labour force employability is a function of educational attainment, we find that tertiary education attainment reduces youth unemployment, with a significant impact on the upper youth labour force, whereas secondary education attainment exacerbates youth unemployment, with a severe impact on the lower youth labour force. The study also finds that persistent youth unemployment discourages young South Africans from pursuing both secondary and tertiary education. As a result, youth unemployment in South Africa is predominantly composed of youthful school leavers. The study findings suggest that South African youths can hedge against unemployment risk through tertiary education attainment, with highly educated graduates having the best labour market prospects.